2021
DOI: 10.1101/2021.02.03.429655
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Horizontal transfer of microbial toxin genes to gall midge genomes

Abstract: A growing body of evidence points to a role for horizontal gene transfer (HGT) in the evolution of animal novelties. Previously, we discovered the horizontal transfer of the gene encoding the eukaryotic genotoxin cytolethal distending toxin B (cdtB) from the Acyrthosiphon pisum Secondary Endosymbiont (APSE) bacteriophage to drosophilid and aphid genomes. Here, we report that cdtB is also found in the nuclear genome of the gall-forming 'swede midge' Contarinia nasturtii (Diptera: Cecidomyiidae). We subsequently… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Endonucleobacter (Supplementary Information Table 1). (iii) Viruses that infect bacteria living inside eukaryotic cells can act as vectors, as shown in some insects that have acquired bacterial toxins through HGT from phages that infect their symbiotic bacteria (Verster et al, 2021) (Supplementary Note 5). Our sequencing analyses revealed that Ca.…”
Section: Ca Endonucleobacter Acquired Inhibitors Of Apoptosis From It...mentioning
confidence: 99%
“…Endonucleobacter (Supplementary Information Table 1). (iii) Viruses that infect bacteria living inside eukaryotic cells can act as vectors, as shown in some insects that have acquired bacterial toxins through HGT from phages that infect their symbiotic bacteria (Verster et al, 2021) (Supplementary Note 5). Our sequencing analyses revealed that Ca.…”
Section: Ca Endonucleobacter Acquired Inhibitors Of Apoptosis From It...mentioning
confidence: 99%